Mathematical Modeling of MHD Flow of CNTs/Ag Nanoparticles Past a Heated Stretchy Surface with Nonuniform Heat Sink/Source and Thermal Radiation Impacts. (17th April 2023) - Gandhimathi, T.; Eswaramoorthi, S.; Loganathan, K.; Mishra, Nirmith Kumar
Abstract : This research communication intends to evaluate the impact of time-dependent MHD Darcy–Forchheimer flow of CNTs/Ag nanoparticles on a heated stretchy surface. Water is employed as a base fluid, and two types of CNTs such as single- and multiwall carbon nanotubes are considered. The significance of nonlinear radiation and heat sink/source is added to our analysis. To accommodate the suitable variables, the governing nonlinear partial differential models are transformed into a set of ordinary differential models. These resulting models are solved analytically and numerically by utilizing the homotopy analysis technique and the bvp4c procedure in MATLAB. The distinctive behavior of pertinent physical parameters on the dimensionless profiles are displayed and discussed through diagrams, tables, and charts. It is discovered that the velocity profile decrepitude whenever there is a change in the unsteady, porosity, and injection/suction parameters. The space and temperature-dependent heat sink/source parameter cause to elevate the thermal profile. The Ag nanoparticles have a lesser surface shear stress compared to both CNTs. The heat transfer gradient develops for larger quantities of radiation and temperature ratio parameters. This research has significant applications in many industrial sectors, such as thermal exchangers, chemical reactors, microelectronics, biomedical engineering, aerodynamics, and industrial production processes.